ANALISIS FAKTOR-FAKTOR PERILAKU PEMBELIAN ONLINE (E-COMMERCE) KONSUMEN MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS PALANGKA RAYA - Deddy Rakhmad Hidayat; Peridawaty Peridawaty (JEMBA : Jurnal Ekonomi Pembangunan, Manajemen dan bisnis, Akuntansi, 2021)
This study was made to examine the determinants of online buying behavior (e-commerce). Factors such as perceived benefits and risks, psychological factors, hedonic motivation and website design are factors that influence the online buying cunsumer behavior. The research method was carried out using a quantitative approach, with collecting data using a questionnaire as a data collection instrument. The respondents used were 100 FEB UPR students in Palangka Raya. The data analysis technique in this study used multiple linear regression with SPSS software. The Result perceived benefits have a significant effect on Online buying Consumer Behavior is accepted. The perceived risks that is accepted has a significant effect on Online Buying Consumer Behavior is accepted. Hedonic motivations has a significant effect on Online Buying Consumer Behavior is accepted. Psychological factors have a significant effect on Online Buying Consumer Behavior is accepted. Website Design has a significant effect on Online Buying Consumer Behavior is accepted. The variables of perceived benefits, perceived risks, hedonic motivations, psychological factors, and Website design simultaneously have a significant effect on online consumer buying behavior